PENGGUNAAN MEDIA PERMAINAN MONOPOLI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VI PADA PEMBELAJARAN IPA MATERI TATA SURYA - Yanti Yuniarti; Nandang Budiman; Novi Ayudyaningtias (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by the low learning outcomes of students as a result of the learning process which is still conventional and without using interactive learning media, so that students are less motivated and learning does not involve students actively. The purpose of this research is to describe the improvement of student learning outcomes in class VI A by using monopoly game media. This research method uses the Collaborative Classroom Action Research (PTKK) method or classroom action research by developing a research design from John Elliot, namely the action is carried out in 3 cycles with data collection carried out through observation sheets, interviews, student worksheets and evaluation tests. The results obtained from the student worksheets in cycle 1 obtained an average of 78.56, cycle II achieved an average of 83.29 and experienced an increase in learning outcomes of 4.73% from cycle 1, cycle III achieved an average of 91.5 and experienced an increase learning outcomes of 8.21%, while the results obtained from evaluation tests in cycle 1 obtained an average of 74.52, cycle II achieved an average of 91.45 and experienced an increase in learning outcomes of 16.93% from cycle 1, cycle III achieved an average an average of 93.53 and experienced an increase in learning outcomes of 2.08%, so that monopoly game media can improve student learning outcomes.